Addressing income inequality and climate change vulnerability in Pune, India: A scenario linkage approach - Jasmin Heilemann; Christian Klassert; Bernd Klauer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2024)
Growing income inequality amplifies social vulnerability to climate change. By linking global with local scenario building for the case of Pune, our approach identifies future trends in inequality and assesses to which degree policy measures considered in Pune account for the climate vulnerability of low-income groups. Rapidly increasing income inequality and the impacts of climate change present substantial challenges for urban areas in low- and middle-income countries, difficult to address by local policymakers. For the case of the Indian city Pune, this study examines the potential effects of future income inequality on social vulnerability to climate change and identifies policy measures that can address these challenges. To this end, we adopt an integrated approach, linking the global scenarios of the Shared Socioeconomic Pathways (SSPs) with local insights and a normative scenario from two workshops held in Pune in 2019. Our findings indicate that income inequality will likely increase, exacerbating the potential social vulnerability of lowincome groups through various channels, e.g. via unequal access to resources and the risk of urban flooding. The policy measures, proposed by local experts, provide suggestions to enhance the resilience of low-income groups in Pune. These policies, however, do not address all previously identified channels to the same degree and partially lack the consideration of systemic aspects to confront growing inequality and climate change impacts
Keywords: 330; Income inequality; climate change vulnerability; scenario design; stakeholder workshops